Smart waste management system for residential area / Nazihah Alway and Asmat Ismail - Alway, Nazihah; Ismail, Asmat (2023)
A growing population, ongoing economic progress, and a greater quality of living have resulted in an unavoidable increase in demand and consumption, resulting in a rise in waste generation. Most researchers concentrated primarily on the final treatment, but few paying attentions to the collection and transportation. Besides, people are confronted with the challenge of waste categorization on MSW, which people must first learn about various forms of waste in order to properly identify them. Without modern waste detection technologies, effective waste sorting and categorization takes longer. The objective of this research is to develop smart waste management system design ideas, to assemble the proposed smart waste management system, to demonstrate the performance of smart waste management system and to suggest the marketability potential of proposed smart waste management system in Malaysia. The research design was quantitative methodology and the data collection method adopted for this study would be based on the document analysis, review the previous literature, design thinking method and 3D modelling. The proposed innovation product for this study was improvised from existing innovation products and various innovation techniques approach which the speciality is for the landed houses with the separation of wastes inside the house. The recommendations for the further studies are the maintenance measure for the underground piping system by using the advance technology and how to ensure the life expectancy of the system for longest time.